Modification of σ‐Donor Properties of Terminal Carbide Ligands Investigated Through Carbide–Iodine Adduct Formation. Issue 40 (9th September 2016) - Reinholdt, Anders; Vosch, Tom; Bendix, Jesper
Abstract: The terminal carbide ligands in [(Cy3 P)2 X2 Ru≡C] complexes (X=halide or pseudohalide) coordinate molecular iodine, affording charge‐transfer complexes rather than oxidation products. Crystallographic and vibrational spectroscopic data show the perturbations of iodine to vary with the auxiliary ligand sphere on ruthenium, demonstrating the σ‐donor properties of carbide complexes to be tunable. Abstract : To give and take : terminal ruthenium carbide complexes [(Cy3 P)2 X2 Ru≡C] (1 ; X=halide or pseudohalide), form charge‐transfer adducts with I2 exhibiting large variation in bond lengths and stretching frequencies. This shows that the auxiliary ligand sphere on ruthenium enables control over the σ‐donor properties of carbide ligands, elucidating their isolobal relationship with carbon monoxide.